Out of The Economic Crises - Mohammad Afifuddin (Advanced Studies on Socio-Economy Development, 2021)
Sidomukti Village, Kebomas District, Gresik Regency, East Java has been known as one of the centers of gold jewelry production which is run traditionally based on the Micro Small Medium Enterprise (MSME) industry. This study aims to describe how changes in the industrial structure were initiated by the gold jewelry craftsmen in Sidomukti as part of the adaptation strategy in facing the economic crisis. The crisis were the decline in the scale of the gold jewelry industry and income due to fluctuations in gold prices since the 1997/1998 monetary crisis. In calculation, the formula applied is the price of gold in the market depends on the exchange rate of the dollar against the rupiah. The lower and more stable the gold price in the market, the more conducive the gold jewelry industry climate. However, since the 1997/1998 monetary crisis, the price of gold in the market tends to rise and is unstable. Using a qualitative research method with a descriptive approach, this study explained the adaptation strategies carried out by the craftsmen in dealing with the crisis. The craftsmen change the structure of the putting out industry that has been going on so far, by modifying the production chain that previously pivoted to the skipper to be more flexible. Craftsmen no longer depend on the production cycle on orders from the skipper, but independently try to produce and market them independently. This study elaborates issues of MSME-based industrial sector resilience and adaptiveness from economic turbulence. Keywords: Adaptation Strategy, Gold Jewelry Industry, Industrial Structure, Putting Out